Posttraumatic Growth (PTG) pada Perawat Penyintas COVID-19 - Dwiyantoro Dwiyantoro; Mustikasari Mustikasari; Ria Utami Panjaitan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study explores Posttraumatic Growth (PTG) in Covid-19 Survivors Nurses at RS X Bandar Lampung. The research method used is qualitative by using phenomenological studies. The results showed that there were six themes in this study. Conclusions, 1) the attitude of nurses who survived Covid-19 towards events that made their heart calmer, 2) the wishes of nurses who survived Covid-19, 3) changes in lifestyle in maintaining health, 4) the impact of Covid-19 on the spiritual aspect, 5) the impact of Covid-19 in carrying out nursing care, 6) the impact of Covid-19 on social aspects. Keywords: Covid-19 Survivors, Nurses, Posttraumatic Growth